Enzymatic Synthesis of Poly(alkylene succinate)s: Influence of Reaction Conditions - Pospiech, Doris; Choińska, Renata; Flugrat, Daniel; Sahre, Karin; Jehnichen, Dieter; Korwitz, Andreas; Friedel, Peter; Werner, Anett; Voit, Brigitte (Basel : MDPI, 2021)
Application of lipases (preferentially Candida antarctica Lipase B, CALB) for melt polycondensation of aliphatic polyesters by transesterification of activated dicarboxylic acids with diols allows to displace toxic metal and metal oxide catalysts. Immobilization of the enzyme enhances the activity and the temperature range of use. The possibility to use enzyme-catalyzed polycondensation in melt is studied and compared to results of polycondensations in solution. The experiments show that CALB successfully catalyzes polycondensation of both, divinyladipate and dimethylsuccinate, respectively, with 1,4-butanediol. NMR spectroscopy, relative molar masses obtained by size exclusion chromatography, MALDI-TOF MS and wide-angle X-ray scattering are employed to compare the influence of synthesis conditions for poly(butylene adipate) (PBA) and poly(butylene succinate) (PBS). It is shown that the enzymatic activity of immobilized CALB deviates and influences the molar mass. CALB-catalyzed polycondensation of PBA in solution for 24 h at 70 °C achieves molar masses of up to Mw~60,000 g/mol, higher than reported previously and comparable to conventional PBA, while melt polycondensation resulted in a moderate decrease of molar mass to Mw~31,000. Enzymatically catalyzed melt polycondensation of PBS yields Mw~23,400 g/mol vs. Mw~40,000 g/mol with titanium(IV)n-butoxide. Melt polycondensation with enzyme catalysis allows to reduce the reaction time from days to 3–4 h. publishedVersion